International orientation and export commitment in fast small and medium size firms internationalization: scales validation and implications for the Brazilian case - Marcelo André Machado (RAUSP Management Journal, 2016)
A set of changes in the competitive environment has recently provoked the emergence of a new kind of organization that has since its creation a meaningful share of its revenue being originated from international activities developed in more than one continent. Within this new reality, the internationalization of the firm in phases or according to its growth has resulted in it losing its capacity to explain this process with regard to small- and medium-sized enterprises (SME). Thus, in this paper, the international orientation (IO) and export commitment (EC) constructs have been revised under a theoretical context of the fast internationalization of medium-sized companies, so as to identify scales that more accurately measure these dimensions in the Brazilian setting. After a literature review and an exploratory research, the IO and EC scales proposed by Knight and Cavusgil (2004) and Shamsuddoha and Ali (2006) were respectively applied to a sample of 398 small- and medium-sized exporting Brazilian companies. In spite of conjunction and situation differences inherent to the Brazilian companies, the selected scales presented high measuring reliability. Furthermore, the field research outcomes provide evidence for the existence of a phenomenon of fast internationalization in medium-sized companies in Brazil, as well as support some theoretical assumptions of other empirical investigations carried out with samples from developed countries.